Acceptability and suitability of alcohol, smoking and substance involvement screening test for older people in the community. Issue 6 (2nd November 2019) - Cusack, Lynette; Kelly, Janet; Groenkjaer, Mette; Wilkinson, Celia; Harland, Jennifer
Abstract : Background: Alcohol use is a common phenomenon within Australian culture. While there has been significant focus on alcohol use among young Australians, there has been little on health promotion or early interventions focussing on older Australians. Methods: This paper presents the findings of an explorative study that used four interactive focus group workshops to ask the question: Is an existing World Health Organisation alcohol and drug screening tool called the Alcohol, Smoking and Substance Involvement Screening Test (originally developed for young people) acceptable and suitable for older people? The data were analysed based on the question using thematic coding. Results: Participants generally considered that they would be more comfortable talking with their health providers about their alcohol and drug use rather than filling out the Alcohol, Smoking and Substance Involvement Screening Test themselves. This suggests that the tool should be modified to accommodate the differences in health status that reflect life events of the different older age groups. Conclusion: Due to potential complex medical and diverse range of pharmacotherapies common among this age group, it is recommended that, if the tool is used, it be administered by health practitioners such as nurses.